Advances in graphene-based electrochemical biosensors for on-site pesticide detection - Zafar, Muhammad Adeel; Waligo, David; Varghese, Oomman K.; Jacob, Mohan V. (Frontiers in Carbon, 2023)
The infiltration of pesticides into agricultural soils has emerged as a critical concern, posing substantial threats to the agriculture industry due to soil and water contamination. The detection of these contaminants is critical towards implementing effective environmental remediation strategies and achieving ecosystem sustainability. Electrochemical sensor technology has been demonstrated to be highly promising for this application. Graphene and its derivatives and composites are widely used as modifying materials in these sensors to enhance their analytical performance. This short review discusses recent progress in the application of graphene-based electrochemical sensors in three-electrode and field-effect transistor configurations for the detection of pesticides posing significant risks to the agricultural sector. It highlights the growing significance of graphene-based sensors in mitigating pesticide-related environmental challenges and underscores their role in ensuring the health and diversity of agricultural ecosystems.